Supply Chain and Logistics in Pandemic - Osorio-Valenzuela, L (Institute of Electrical and Electronics Engineers Inc., 2021)
This research work has the purpose of analyzing and proposing strategies that allow to face the complexities brought by the pandemic within a supply chain. Under the context of the Covid 19 pandemic, a scenario analysis is carried out to propose strategies adaptable to similar problems. It was identified that those companies that had prior planning to deal with eventualities managed to overcome the effects of the crisis with greater success. This work highlights the need for companies to know and incorporate strategies that allow sustainability in the long term. © 2021 IEEE.